Diseño arquitectónico de envolventes sostenibles en antiguos edificios generadores de islas de calor en climas estacionales. (2022)
Currently we observe that global warming and the increase in heat islands are affecting daily life, generating unfavorable microclimates for the planet. Pollution is generated due to a lack of sustainable design in the first buildings and because the impact that these would generate on its citizens was not anticipated both inside the space and outside the buildings; the use of fossil fuels as power generators for heating elements among others, help to increase heat islands where large buildings are located New York City as the main city of skyscrapers in the Manhattan sector this problem is observed and it is sought that through a theoretical analysis a replicable model of an adaptable envelope is implemented from the implementation of sustainable materials and its own design; generating an integral and comfortable relationship between the interior and exterior in order to solve the needs of said pre-existing building.